Implementation of Competence, Remuneration on Employee Performance in Warehousing Logistics: Literature Review - Esti Liana; Hartono (East Asian Journal of Multidisciplinary Research, 2023)
This paper aims to determine the implementation of variables in the logistics field by searching the literature in journals. Qualitative by searching the literature related to the variables related to this paper in the last ten years and the findings will be corroborated in this paper both quantitative and qualitative findings. The results of this paper are used as a reference for logistics warehousing companies in Jakarta. Logistics warehousing companies can use the findings in this paper with a qualitative description of the literature in accordance with the variables written and provide a treasure and contribution in the field of human resources. For other researchers, they can develop and use the variables in this paper with existing gaps in the literature to continue future research with the object of logistics companies.